PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA GURU EKONOMI SMA NEGERI SE-KOTA PONTIANAK - Darmanto, Primanita Putri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract : The purpose of this research to know and (1) the influence of compensation to teacher performance (2) the influence of work discipline to teacher performance (3) the influence of compensation to work discipline (4) the influence of compensation and discipline work to teacher performance. Method of data analysis using descriptive analysis, linearity test, and multiple linear regression analysis. Method of data collection using questionnaires and documentation. The sample in this research is the economics teacher of  senior high school in  Pontianak city. The results of the classic assumption test show the residual values are normally distributed. there is no multicolinearity and heteroscedasticity. The result of multiple linear regression analysis showed that the compensation and work discipline positif influence on teacher performance.The conclusions of this research is (1) There is a positive effect of compensation on teacher performance with coefficient determination of71,19% (2) There is a positive influence of work discipline on teacher performance with coefficient determination of 84,75% (3) There is a positive effect of compensation on work discipline with value of sig. 0,073 > 0,050 (4) There is a positive influence of compensation and work discipline on teacher performancewith coefficient determination of 47,6%.Keywords: Compensation, Discipline Work, Performance Teacher.